Update and extension of the When2Heat dataset - Oliver Ruhnau; Jarusch Muessel (ZBW – Leibniz Information Centre for Economics, 2022)
The "When2Heat" dataset comprises synthetic national time series for heat demand and heat pumps' coefficient of performance (COP) in hourly resolution. Heat demands for space and water heating are computed by combining gas standard load profiles with spatial temperature reanalysis data and population geodata. With this update, we extend the dataset to 28 European countries and the period from 2008 to 2019, including new, state-of-the-art data sources. For the geographical extension, we propose a novel approach, shifting established German heat demand curves based on country-specific heating thresholds to account for regional differences in thermal insulation and user behavior. Using the example of Italy, we illustrate the effect of shifting heat demand curves. The dataset, scripts, and input parameters are publicly available under an open-source license on the Open Power System Data platform.
Additional information: This is an update and extension of the original When2Heat dataset described in: Ruhnau, O., Hirth, L., Praktiknjo, A., 2019. Time series of heat demand and heat pump efficiency for energy system modeling. Sci Data 6, 189. https://doi.org/10.1038/s41597-019-0199-y
Keywords: 330; Heat demand; Heat pumps; Coefficient of performance; Europe